2014
DOI: 10.1177/1071100714552077
|View full text |Cite
|
Sign up to set email alerts
|

Staged Treatment of High Energy Midfoot Fracture Dislocations

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Any dislocation-producing tension on the overlying skin and soft tissue envelope should be immediately reduced and immobilized. Temporary external fixation may be utilized in the event of a high-energy injury, particularly if provisional alignment cannot be maintained in a splint [9]. Definitive surgery is generally delayed 10 to 14 days to allow adequate resolution of soft tissue swelling.…”
Section: Unstable Injuriesmentioning
confidence: 99%
“…Any dislocation-producing tension on the overlying skin and soft tissue envelope should be immediately reduced and immobilized. Temporary external fixation may be utilized in the event of a high-energy injury, particularly if provisional alignment cannot be maintained in a splint [9]. Definitive surgery is generally delayed 10 to 14 days to allow adequate resolution of soft tissue swelling.…”
Section: Unstable Injuriesmentioning
confidence: 99%
“…An external fixator would be an alternative for fixation. Kadow et al reported that external fixators were effective to protect the length and alignment during staged treatment of midfoot fracture/dislocations (12). But we anticipated that the second stage would be closer and K-wire fixation would be enough for temporary fixation.…”
Section: Discussionmentioning
confidence: 86%
“…Attempts at early definitive fixation of highenergy injuries have been shown to result in an increased rate of complications, including skin slough and deep infection [7,9,22,30]. Conversely, staged fracture care (provisional external fixation followed by definitive internal fixation) has been shown to result in favorable functional outcomes with decreased rates of soft tissue complications [10,18,29,34].…”
Section: Descriptionmentioning
confidence: 99%